Increases in Human Papillomavirus Testing Preceding Diagnosis of Cervical Precancer in 5 US States, 2008–2016. Issue 3 (July 2021) - Cleveland, Angela A.; Gargano, Julia W.; Griffin, Marie R.; Park, Ina U.; Niccolai, Linda M.; Bennett, Nancy M.; Pemmaraju, Manideepthi; Fink, Deanna; Brackney, Monica; Scahill, Mary; Ehlers, Sara J.; Unger, Elizabeth R.; et al.
Abstract : Objective: The aim of the study was to describe trends in human papillomavirus (HPV) testing preceding diagnosis of cervical precancer during a time of changing screening recommendations. Materials and Methods: We conducted a cross-sectional analysis of data from active, population-based, laboratory surveillance among 1.5 million residents of 5 areas in the United States. We included women aged 21–39 years diagnosed with cervical intraepithelial neoplasia grades 2, 2/3, or 3 or adenocarcinoma in situ (collectively, CIN2+) during 2008–2016, who had a cytology and/or HPV test before diagnosis ( n = 16, 359). Results: The proportion of women with an HPV test preceding CIN2+ increased from 42.9% in 2008 to 73.3% in 2016 ( p < .01); testing increased in all age groups (21–24 y: 35.3% to 47.6%, 25–29 y: 40.9% to 64.1%, 30–39 y: 51.7% to 85.9%, all p < .01). The HPV testing varied by cytology result and was highest among women with atypical squamous cells of unknown significance ( n = 4, 310/4, 629, 93.1%), negative for intraepithelial lesion or malignancy ( n = 446/517, 86.3%), and atypical glandular cells ( n = 145/257, 56.4%). By 2016, at least half of all cases in every surveillance area had an HPV test before diagnosis. Conclusions: During 2008–2016, the proportion of women with an HPV test preceding CIN2+ increased significantly for all age groups, cytology results, and surveillance areas. By 2016, most (85.9%) women aged 30–39 years had an HPV test, consistent with recommendations. Increasing utilization of HPV tests, which have demonstrated improved sensitivity for detecting cervical disease, may in part explain increasing rates of cervical precancer among women 30 years and older.